2023
DOI: 10.3390/ijms241814121
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Tampons Are Reliable and Acceptable Tools to Self-Collect Vaginal Microbiome Samples

Florence Turner,
Josephine Drury,
Dharani K. Hapangama
et al.

Abstract: Many women report embarrassment as the cause for their avoidance of routine gynaecological screening appointments. Methods of self-collection of bio samples would perhaps encourage women to participate in routine screening programs. The vaginal microbiome plays a key role in women’s health and reproductive function. Microbial disturbances can result in the loss of lactobacillus dominance, also known as dysbiosis, associated with an increased risk of contracting sexually transmitted infections (STIs), pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Despite the sampling methods possibly having an impact on the number of cells and DNA collected, the microbiome features were equivalent within the same patient. Other studies compared the microbial diversity between the self-collected swabs or tampons with the physician-collected samples [ 19 , 20 ]. Our results are aligned with previous research, indicating that no differences were found between the SCS and LBC samples, neither in the alpha nor beta diversity analyses ( Figure 1 b,c).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the sampling methods possibly having an impact on the number of cells and DNA collected, the microbiome features were equivalent within the same patient. Other studies compared the microbial diversity between the self-collected swabs or tampons with the physician-collected samples [ 19 , 20 ]. Our results are aligned with previous research, indicating that no differences were found between the SCS and LBC samples, neither in the alpha nor beta diversity analyses ( Figure 1 b,c).…”
Section: Discussionmentioning
confidence: 99%